Riyadlah Dzikir, Al-Qur’an dan Praktik Garapan Jama’ah Darul Iman Purwakarta - Mustofa, Badrun; Fitriana, Muhammad Azizan; Shofia , Siti (JOM, 2024)
The prevalence of mental and psychological issues among Muslims is often attributed to their lack of remembrance of God. Riyadlah dhikr, as a spiritual practice aimed at remembering God, is considered a pivotal solution to this issue. Despite various forms of dhikr being practiced across the archipelago, the specific utilization of Qur'anic verses in Riyadhoh dhikr remains underexplored. This study investigates the impact of Riyadhoh dhikr practices using Qur'anic verses, referred to as "garapan," and explores their benefits for participants. Employing a Sufi perspective, the study utilized qualitative methods, including field assessments and interviews with members of Majelis Dzikir Darul Iman Purwakarta. The findings reveal that Riyadhoh dhikr serves not only as a means to purify the heart (qolbu) and draw closer to Allah through repentance and munajat, but also as a garapan practice within Majelis Dzikir Darul Iman, involving both physical and spiritual fasting, and secluded devotional sessions (uzlah) for dhikr in mosques or prayer rooms using Surah Al-Fatihah and Al-Ikhlas as spiritual conduits under the guidance of a mentor. These practices exemplify the integration of Qur'anic principles in Sufi traditions, offering an alternative for Muslim communities grappling with life's challenges. Darul Iman, renowned for its scholarly heritage in dhikr, is dedicated to disseminating Islamic teachings through Sufi practices, evident in its extensive network of branches throughout Indonesia.